THE GROWTH RESPONSE OF CAULIFLOWER PLANTS (BRASSICA OLERACEA) USING OF BOTANICAL PESTICIDE - Rahmawati, Lina; Maghfirah, Putri; Diannita (Barkah Publishing, 2025)
Cauliflower (Brassica oleracea) is one of the most widely cultivated and profitable horticultural plants. During the growth of cauliflower plants, various pest attacks can disrupt the harvest. This study examines the growth response of cauliflower plants to the use of botanical pesticides (Azadiractica indica) for pest control. In this study, a Randomized Block Design (RBD) was used, which had five treatments and five replications, namely: P0 as the control (without applying neem leaf solution), P1 provides a neem leaf solution of 300 ml/1000 ml of water (30%), P2 provides a neem leaf solution of 500 ml/1000 ml of water (50%), P3 provides a neem leaf solution of 700 ml/1000 ml of water (70%), and P4 provides a neem leaf solution of 900 ml/1000 ml of water (90%). The highest damage from the Plutella xylostella caterpillar attack was observed in the P0 (Control) treatment, because in this treatment, no spraying of neem leaf pesticide solution was conducted, causing the Plutella xylostella caterpillar to continuously attack the cauliflower plants, resulting in severe damage to the leaves and stems of the cauliflower plants.The cauliflower plants that were not treated experienced damage to their leaves, with the leaves being completely eaten and a large number of pests continuously attacking the untreated cauliflower plants.